2010
DOI: 10.1158/1535-7163.mct-10-0051
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Induces Apoptosis by a Bak-Dependent Intrinsic Pathway

Abstract: The sesquiterpene lactone dihydroartemisinin (DHA), a semisynthetic derivative of the herbal antimalaria drug artemisinin, is cytotoxic to human tumor cells. Treatment of Jurkat T-lymphoma cells with DHA induced a breakdown of the mitochondrial transmembrane potential, release of cytochrome c, activation of caspases, and DNA fragmentation indicative of apoptosis induction. Although the absence of FADD or caspase-8 did not alter apoptosis rates in Jurkat cells, overexpression of dominant-negative caspase-9 or o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 55 publications
6
67
0
Order By: Relevance
“…DHA, a semi-synthetic derivative of the herbal antimalarial drug artemisinin, can obviously inhibit the growth of a variety of cancer cells, including breast cancer, leukemia, cervical cancer, ovarian cancer, lung cancer, gliomaand oral cancer (Jiao et al, 2007;Nam et al, 2007;Mu et al, 2008;Chen et al, 2009;Handrick et al, 2010). Our studies indicated that DHA inhibited the growth of A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…DHA, a semi-synthetic derivative of the herbal antimalarial drug artemisinin, can obviously inhibit the growth of a variety of cancer cells, including breast cancer, leukemia, cervical cancer, ovarian cancer, lung cancer, gliomaand oral cancer (Jiao et al, 2007;Nam et al, 2007;Mu et al, 2008;Chen et al, 2009;Handrick et al, 2010). Our studies indicated that DHA inhibited the growth of A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 60%
“…DHA is shown to have anticancer effects in a wide variety of cancer models in vitro and in vivo (Jiao et al, 2007;Sun et al, 2014). Many studies have shown that DHA inhibits cell proliferation, and induces apoptosis in various human cancer cell lines via down-regulating cyclin (D1, E), Bcl-2, Bcl-xL, caspase-3, caspase-9 and VEGF, while up-regulating P21, P27 and Bax (Nam et al, 2007;Mu et al, 2008;Chen et al, 2009;Chen et al, 2010;Handrick et al, 2010). Therefore, the targeted efficacy of DHA on the TCTP expression of lung cancer cell was explored in the study.…”
Section: Targeted Efficacy Of Dihydroartemisinin For Translationally mentioning
confidence: 99%
“…DHA could also inhibit the Wnt/β-catenin signaling pathway in lung cancer, and the expressions of key proteins including Wnt5-a/b, LRP6 and Dvl2 in the Wnt/β-catenin signaling pathway were significantly decreased (27). More importantly, DHA has been shown to increase reactive oxygen species generation, downregulate transferrin receptor mRNA expression and telomerase activity, upregulate NOXA protein in T-cell lymphoma cells (13,28). We intend to study the mechanisms underlying the effects of DHA on NOXA signaling in T cell lymphoma cells in future.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that DHA exerts its anticancer action by increasing the expression of interferon-γ and decreasing the level of interleukin-4 (6). The majority of reports concerning the mechanisms underlying DHA have focused on DHA-induced apoptosis (7,8). Chen et al (7) reported that ARS and its derivatives, particularly DHA, were potently cytotoxic to human ovarian cancer A2780 and OVCAR-3 cells through the death receptor and mitochondrial-mediated caspase-dependent apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (7) reported that ARS and its derivatives, particularly DHA, were potently cytotoxic to human ovarian cancer A2780 and OVCAR-3 cells through the death receptor and mitochondrial-mediated caspase-dependent apoptotic pathways. Handrick et al (8) demonstrated that DHA induced the activation of caspases and DNA fragmentation in Jurkat T-lymphoma cells, which would induce apoptosis. In addition, DHA has been identified to induce autophagy in cancer cells: Hu et al (9) and Jia et al (10) demonstrated that DHA has the ability to induce autophagy and exert anticancer activities in cell lines of various types of cancer, including the human multiple myeloma cancer RPMI 8226 cell line, promyelocytic leukemia NB4 cell line, human colorectal cancer HCT116 cell line, human cervical cancer HeLa cell line and the human pancreatic cancer cell lines BxPC-3 (CRL-1687) and PANC-1 (CRL-1469).…”
Section: Introductionmentioning
confidence: 99%